An assessment of EU Cohesion Policy in the UK regions: direct effects and the dividend of targeting - Di Cataldo, Marco; Monastiriotis, Vassilis (London, 2018)
"With the prospective exit of the UK from the European Union, a crucial question is whether EU Structural Funds have been beneficial for the country and which aspects of Cohesion Policy should be maintained if EU funds are to be replaced. This paper addresses this question through a twofold investigation, assessing not only whether but also how EU funds have contributed to regional growth in the UK over three programming periods from 1994 to 2013. We document a significant and robust effect of Cohesion Policy in the UK, with higher proportions of Structural Funds associated to higher economic growth both on the whole and particularly in the less developed regions of the country. In addition, we show that the strategic orientation of investments also plays a distinct role for regional growth. While concentration of investments on specific pillars seems to have no direct growth effects, unless regions can rely on pre-existing competitive advantages in key development areas, we unveil clear evidence that targeting investments on specific areas of relative regional need has a significant and autonomous effect on growth. These findings have important implications for the design of regional policy interventions in Britain after Brexit."